Metabolism of tumor infiltrating T cells - Ertl, Hildegund CJ (Frontiers in Immunology, 2026)
The microenvironment of solid tumor is commonly low in key nutrients such as glucose providing metabolic challenges for tumor infiltrating T lymphocytes (TIL), which upon activation switch to glycolysis to meet their need for energy and effector molecule production. Consequently, TIL become functionally impaired and die unless they can switch their metabolism to alternative pathways such as oxidative phosphorylation catabolizing lipids that are in ample supply within solid tumors. Medicinal interventions that alter the nutrient supply within tumors or that facilitate the TIL’s metabolic switch away from glycolysis have been tested in experimental animals and clinical trials. Some of them were shown to increase TIL functions, prolong their survival and enable them to slow tumor progression.